2009
DOI: 10.1007/978-3-642-00298-4
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological and Air Quality Models for Urban Areas

Abstract: Urban features essentially influence atmospheric flow and microclimate, strongly enhance atmospheric turbulence, and modify turbulent transport, dispersion, and deposition of atmospheric pollutants (e.g., Piringer et al., 2007). Increased resolution in numerical weather prediction (NWP) models allows for a more realistic reproduction of urban air flows and air pollution processes, however most of the operational models still do not consider, or consider very poorly, the urban effects. This has triggered new in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 26 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Urban features (e.g., sizes of buildings and overall morphology, distribution of streets, total dimension of urban area) affect low-level atmospheric flow and hence influence turbulence and the dispersion of airborne pollutants and their deposition (Baklanov et al 2009). The simulation of airflow distribution constitutes a challenge whenever ADMs are used to better understand and/or predict the pollutant dispersion in an urban environment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Urban features (e.g., sizes of buildings and overall morphology, distribution of streets, total dimension of urban area) affect low-level atmospheric flow and hence influence turbulence and the dispersion of airborne pollutants and their deposition (Baklanov et al 2009). The simulation of airflow distribution constitutes a challenge whenever ADMs are used to better understand and/or predict the pollutant dispersion in an urban environment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this progress, a wide range of ADMs can now simulate air pollution dispersion in cities (e.g. Baklanov et al 2009;Lateb et al 2016;Wingstedt et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The single-layer urban canopy models (SLUCMs) simulate the urban energy fluxes at one atmospheric layer representing the city below the roof level. The multilayer models, on the other hand, simulate the energy fluxes at several atmospheric layers that interact with the buildings within the UCL (Grimmond et al, 2009;Masson, 2006).…”
Section: Urban Canopy Modelsmentioning
confidence: 99%
“…Air temperature and humidity are assumed to be uniform in the UCL. For the wind, the logarithmic law is applied down to just under the top of the canyon and the exponential law is used below (Grimmond et al, 2009;Masson, 2006). Despite the simplification approaches, the SLUCMs that primarily developed for applications in mesoscale modeling (Kusaka et al, 2001;Masson, 2000) have shown a good performance in simulating the sensible heat fluxes and the surface and air temperatures over built-up areas (Masson et al, 2002;Kusaka and Kimura, 2004).…”
Section: Single-layer Urban Canopy Modelsmentioning
confidence: 99%
See 1 more Smart Citation